Toward an animal model of Progressive Supranuclear Palsy - Priyanka,; Qamar, Syeda Hania; Visanji, Naomi P. (Frontiers in Neuroscience, 2024)
Progressive Supranuclear Palsy (PSP) is a rare and fatal neurodegenerative tauopathy which, with a rapid clinical progression coupled to a strong degree of clinico-pathologic correlation, has been suggested to be a “frontrunner” in translational development for neurodegenerative proteinopathies. Elegant studies in animals have contributed greatly to our understanding of disease pathogenesis in PSP. However, presently no animal model replicates the key anatomical and cytopathologic hallmarks, the spatiotemporal spread of pathology, progressive neurodegeneration, or locomotor and cognitive symptoms that characterize PSP. Current models therefore likely fail to recapitulate the key mechanisms that underly the pathological progression of PSP, impeding their translational value. Here we review what we have learned about PSP from work in animals to date, examine the gaps in modeling the disease and discuss strategies for the development of refined animal models that will improve our understanding of disease pathogenesis and provide a critical platform for the testing of novel therapeutics for this devastating disease.